PENGARUH KETERLIBATAN KERJA DAN PEMBAGIAN KERJA TERHADAP KINERJA PEGAWAI PADA PEMERINTAHAN KECAMATAN SIBOLGA KOTA - Harmoko W Purba; Mansur Tanjung; Yacub Hutabarat (CV. ALIM'SPUBLISHING, 2023)
The organization is a means or tool for achieving goals, as a vehicle (vehicle) for the activities of workers who work together in their efforts to achieve goals. These goals certainly differ from one another, for example, they can be in the form of social services, education improvement, career development and so on. Every activity carried out by an organization certainly requires various resources, such as capital, materials, and machinery. Existing resources will be meaningless if not managed properly. To manage it requires other resources, namely, human resources. The formulation of the problem in this study is the formulation of whether work involvement and division of labor jointly affect the performance of employees in the Sibolga Kota District Government? This study aims to determine how much influence work involvement and division of labor have on employee performance in the Sibolga Kota District Government. The temporary hypothesis is that work involvement and division of labor have a joint effect on the performance of employees in the Sibolga Kota District Government. The population is 85 people and is used as a sample. Data collection techniques using library research and field research. The results of the study show that the variables of work involvement and division of labor can affect the performance of employees in the Sibolga Kota District Government by 54.2%. Work involvement and division of labor jointly or simultaneously have a positive and significant effect on the performance of employees in the Sibolga Kota District Government. Where the Fcount value is greater than the Ftable value (38.510 > 3.11). Partially, work involvement has a positive and significant effect on employee performance in the Sibolga Kota District Government. Where the value of tcount = (2.373) is greater than the value of ttable (1.992), Partially the most dominant division of labor affects employee performance, meaning that the variable of division of labor is more decisive in improving employee performance compared to work involvement. Where the value of tcount = (4.453) is greater than the value of ttable (1.995).